Strategi Mengatasi Penyebab Surging Mesin Diesel Penggerak Utama di MT. ONTARI - Afdolludin Afta Tazani (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2019)
Turbocharger is a component to increase the amount of air that enters the cylinder by using exhaust gas energy. Very high quality gas turbocharger.The research method used in this research is descriptive qualitative method. Data analysis techniques use the SWOT method to analyze the factors that cause surging of the Main Movers Diesel Engine and the efforts made to overcome the factors associated with strengthening, weakness, opportunities, and protection.Based on the results of research conducted by researchers, the cause of the rise in Diesel Engine The main driving force is caused by two factors, namely the escape of compression during combustion due to oversize cylinder liner and spare parts of the main engine supply on the ship is hampered. To overcome the factors that can be done using cylinder liner that has been oversized, reducing the rotation of the main engine so that the exhaust gas is more stable, reducing the consumption of cylinder oil to reduce sludge in the rinse air chamber, using a blower to be manual to increase the rinse air to normal pressure during the engine operation, reconditioning the spare parts Parent engines such as crown pistons and piston rings by repairing so that they can be used again temporarily waiting for parts to arrive on board, and making spare parts purchases with boat money on spare parts that are lightweight and inexpensive for maintenance and repair of main engine spare parts.